2023
DOI: 10.1002/phar.2791
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nimodipine formulations and administration techniques via enteral feeding tubes in patients with aneurysmal subarachnoid hemorrhage: A multicenter retrospective cohort study

Abstract: Background: Nimodipine improves outcomes following aneurysmal subarachnoid hemorrhage (aSAH) and current guidelines suggest that patients with aSAH receive nimodipine for 21 days. Patients with no difficulty swallowing will swallow the whole capsules or tablets; otherwise, nimodipine liquid must be drawn from capsules, tablets need to be crushed, or the commercially available liquid product be used to facilitate administration through an enteral feeding tube (FT). It is not clear whether these techniques are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…We previously reported an association between the nimodipine administration technique and patient outcomes where patients receiving crushed nimodipine tablets enterally had worse outcomes compared to those who received whole tablets after controlling for disease severity (57). We confirmed such findings in a multicenter retrospective study where we compared various enteral administration formulations and techniques (22). This could be attributed to the reduced oral bioavailability of enteral nimodipine, especially the manufacturer recommends against tablet crushing due to the risk of reduced absorption (58).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…We previously reported an association between the nimodipine administration technique and patient outcomes where patients receiving crushed nimodipine tablets enterally had worse outcomes compared to those who received whole tablets after controlling for disease severity (57). We confirmed such findings in a multicenter retrospective study where we compared various enteral administration formulations and techniques (22). This could be attributed to the reduced oral bioavailability of enteral nimodipine, especially the manufacturer recommends against tablet crushing due to the risk of reduced absorption (58).…”
Section: Discussionsupporting
confidence: 65%
“…All of the comparisons were not statistically different, except for (−)-R and total nimodipine among the participants who presented with high grades. (+)-R nimodipine AUC 0-3h in those who did not develop vasospasm were 4-fold significantly higher than those who had vasospasm [83(64-138) vs. 23 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) ng.h/mL, respectively, value of p = 0.047]. Similarly, (−)-R nimodipine C max in those who did not develop vasospasm were 4-fold significantly higher than those who had vasospasm [34(24-83) vs. 9 (6)(7)(8)(9)(10)(11) ng/mL, respectively, value of p = 0.009].…”
Section: Nimodipine Exposure and Patient Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor, We are writing in response to a recent article published by Mahmoud et al, which found that enteral nimodipine formulations are not equivalent across multiple endpoints, such as the incidence of diarrhea and need for dosage reduction. 1 We would like to share our experience of successfully implementing in-house compounding of nimodipine oral syringes, given the favorability found in the endpoints studied and associated cost savings.…”
mentioning
confidence: 99%